Exploring the nature of physician leadership for family medicine resident physicians: a phenomenological study - Dewsnap, Michael A., author; Lynham, Susan A., advisor; Arroliga, Alejandro C., committee member; Coates, Tabitha L., committee member; Hooper, Barbara R., committee member (Colorado State University. Libraries, 2020)
From solo practitioner in the late 19th century to team leader and policy maker in the 21st century, the physician's role is becoming increasingly complex and often extending beyond the perceived traditional realm of patient care. Such complexity has garnered recent attention for defining and developing physician leadership in order to equip physicians to lead in the shifting landscape of health care. Nonleader resident physicians are an underrepresented population in the literature on physician leadership. Although a few resident physicians assume formal leadership roles in medical residency, the majority serve as leaders by virtue of their stage in training or as informal leaders to peers and others. Little is known about resident physicians not in formal roles (nonleaders) and how they describe physician leadership through their lived experiences in graduate medical education. This study explored the nature of physician leadership for nonleader family medicine resident physicians from their descriptions of physician leadership. Guided by the constructivist paradigm, the research question for this qualitative study was, How do family medicine resident physicians describe and experience the nature of physician leadership? The conceptual framework consisted of (a) two foundational leadership elements, (b) leadership era paradigms, and (c) three contexts of medical education. Descriptive phenomenology was selected as the methodology and data were collected from six family medicine residents in two family medicine residency programs in a southwestern state in the United States. The participants met criteria and completed two rounds of interviews and member checking. The data were analyzed through integrative data analysis and yielded themes about what was experienced regarding physician leadership, such as (a) the environment created by physician leaders, (b) the attributes and behaviors of physician leaders, and (c) the focus on the followers. These themes were bound by how the resident physicians experienced these aspects, such as through the context of the specialty of family medicine, the graduate medical education context, and the apprenticeship structure of medical residency that facilitated day-to-day proximity to physician leaders. Conclusions and recommendations for practice, future research, and theorizing are also presented.
Keywords: lived experience; physician; resident physicians; phenomenology; leadership; qualitative research